El teatro infantil en la educación inicial. - Nieto Chiliguano, Lorena Margarita (2018)
The present research had as reference the infantile theater‟s study in the initial education at Milenio Alóag Educational Unit in the academic year 2017 - 2018, seeing that the theater is an artistic expression that will allow that the children express their emotions and feelings, will help to improve language, body language and improve peer relationships. The objective of the study was to determine the importance of the theater in the initial education level, the research is projected in the most recurrent problems that can be presented to teachers at classroom, it is not finding the appropriate didactic resources which allow that the teaching-learning process is reflected in competences for the integral development of the children, in this way the students. When practicing different theatrical activities, will allow them to be more active, creative and imaginative in their daily living Nowadays the limited use of children's theater has meant that people do not appreciate theatrical art, the teachers in the institutions do not practice children's theater; because for the children the classes become monotonous which does not allow them to develop their skills and abilities, there is a limited formation of the technique of the children's theater seeing that the teachers have difficulty in teaching a fun and entertaining class, for this reason the children's theater do not use as a teaching-learning strategy. As a consequence teaching traditional, as a result the children will lose interest for learning and feel afraid to participate in activities that are performed as role play and theater performance. The impact of this research was of social service for this make known the importance that has theater within the classroom, be this will help to reinforce learning and also know the benefits that theater provides children On the other hand, it pretend to guide the teacher and encourage the need to continually train on the correct practice of theater and the application of new and appropriate strategies to favor infants to increase the development of language and socio-affective development.